Understanding the Experiences of Racially Minoritized Doctoral Students in Evangelical Theological Education - Espinoza, Benjamin D. (Christian higher education, 2021)
Although some scholars have explored the experiences of racially minoritized doctoral students in large research universities, few have studied the racial dynamics of doctoral education in smaller institutions. Evangelical seminaries, graduate-level schools that train people for religious vocations, have become the subject of racial criticism in recent years. To better understand the racial dynamics of doctoral education in evangelical seminaries, I conducted a narrative-driven qualitative study with 12 racially minoritized doctoral students from several of these institutions. Employing a conceptual lens of Critical Race Theory (CRT) and Yancey’s definitions of racism, I argue that racially minoritized doctoral students in evangelical seminaries remain under-supported in various ways.